2010
DOI: 10.1093/gerona/glq053
|View full text |Cite
|
Sign up to set email alerts
|

Complex Mental and Physical Activity in Older Women and Cognitive Performance: A 6-month Randomized Controlled Trial

Abstract: In healthy older women, participation in new stimulating activities contributes to cognitive fitness and might delay cognitive decline. Exercise and computer classes seem to generate equivalent beneficial effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
143
2
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(161 citation statements)
references
References 33 publications
8
143
2
8
Order By: Relevance
“…Health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al 2008), better functional, physical, and psychosocial health (Taylor et al 2004;Hughes et al 2004), more positive affect (Netz et al 2007), reduced risk of falling (Carter et al 2001), better health-related quality of life (Rejeski and Mihalko 2001;Motl and McAuley 2009), and less cognitive decline (Klusmann et al 2010). However, despite this evidence, many older adults are not sufficiently active to enjoy these health benefits (Newsom et al 2004).…”
Section: Physical Activity and Health In Old Agementioning
confidence: 99%
“…Health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al 2008), better functional, physical, and psychosocial health (Taylor et al 2004;Hughes et al 2004), more positive affect (Netz et al 2007), reduced risk of falling (Carter et al 2001), better health-related quality of life (Rejeski and Mihalko 2001;Motl and McAuley 2009), and less cognitive decline (Klusmann et al 2010). However, despite this evidence, many older adults are not sufficiently active to enjoy these health benefits (Newsom et al 2004).…”
Section: Physical Activity and Health In Old Agementioning
confidence: 99%
“…Young and, mainly, older adults with a high educational status (HES) had better dual-task performances on lower limb alternation from the ground to a step and simultaneous visual discrimination of two targets on a screen 23,24 . The educational status has also been associated with ability on some tasks involving balance and gait in older adults 25,26 . We hypothesized that cognitive-motor tasks involving lower limb function could minimize the influence of education.…”
mentioning
confidence: 99%
“…The participation of older adults in new stimulating activities, e.g. a computer course or an exercise program, might delay cognitive decline 25,26,27 . The knowledge of how age and education interact in cognitive-motor learning might complement the theories of brain and cognitive reserves.…”
mentioning
confidence: 99%
“…This suggests an interaction between environment and the brain as a consequence of adaptation. The most consistent improvements of fluid cognition in older age were found in studies investigating effects of physical aerobe exercise across several months (Colcombe and Kramer 2003;Colcombe et al 2004;Erickson et al 2011;Klusmann et al 2010;Kramer et al 1999Kramer et al , 2006Kramer and Erickson 2007;VoelckerRehage et al 2010VoelckerRehage et al , 2011; see also Hillman et al 2008 for review). Colcombe et al (2004) found particular improvements of so-called executive functions and working memory, i.e.…”
Section: General Factors Affecting Cognitive Functions In Agingmentioning
confidence: 87%